PENGEMBANGAN PERMAINAN LUDO EDUKASI SEBAGAI MEDIA ALTENATIF PEMBELAJARAN PAI KELAS VIII DI SMPN 2 PERAK JOMBANG - Khoirun Nisa'; Zakiyaturrosyidah; Waslah (Prodi Pendidikan Agama Islam Sekolah Tinggi Agama Islam Daruttaqwa Gresik, 2021)
ABSTRACT: This research is a field research that examines the development of educational ludo games as an alternative media for learning Islamic education for class VIII at SMPN 2 Perak Jombang. This study aims to: (1) develop learning media for educational ludo games on Islamic religious education learning materials. (2) Knowing the feasibility of learning media for educational ludo games. This research is a development research (R&D) with a 4-D model of S. Thiagarajan, Dorothy S. Semmel, and Melvyn I. Sammmel which has 4 stages, namely: define, design, develop, and disseminate. (deployment). The feasibility of learning media for educational ludo games is seen from the average score of validator assessments and student responses. The results of this study indicate that: (1) the way to develop this educational Ludo game media is to use the 4-D stage. (2) The results of this study are the development of this educational Ludo game is suitable for use in learning. The feasibility of the product is based on the assessment of material experts and media experts with a percentage assessment of 85% in the very feasible category and 89% in the very feasible category and the results obtained from research on content quality aspects, the percentage of feasibility, are 95% in the very feasible / interesting category. Based on the table the significant value of the prites and posttests is 0.25, so it can be interpreted that the conclusion of H0 is rejected because there is no significant difference between learning using ludo-educational and non-educational learning media. Therefore H1 is accepted because there is a significant difference between learning using educational ludo game media Keywords: Game, Ludo, Education